Mycobacterium tuberculosis Pathogenesis, Infection Prevention and Treatment - Ferraris, Davide Maria; Miggiano, Riccardo; Rizzi, Menico (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis (MTB) and it represents a persistent public health threat for a number of complex biological and sociological reasons. According to the most recent Global Tuberculosis Report (2019) edited by the World Health Organization (WHO), TB is considered the ninth cause of death worldwide and the leading cause of mortality by a single infectious agent, with the highest rate of infections and death toll rate mostly concentrated in developing and low-income countries. We present here the editorial section to the Special Issue entitled "Mycobacterium tuberculosis Pathogenesis, Infection Prevention and Treatment" that includes 7 research articles and a review. The scientific contributions included in the Special Issue mainly focus on the characterization of MTB strains emerging in TB endemic countries as well as on multiple mechanisms adopted by the bacteria to resist and to adapt to antitubercular therapies.